Motivation, Discipline, and Academic Performance in Physical Education: A Holistic Approach From Achievement Goal and Self-Determination Theories - Claver, Fernando; Martínez-Aranda, Luis Manuel; Conejero, Manuel; Gil-Arias, Alexander (Frontiers in Psychology, 2020)
The analysis of disciplined behaviors and academic performance in school context has become one of the main concerns within the educational community. Physical Education is highlighted as a key subject to analyze students’ behavior. Researchers and Physical Education teachers are interested on the motivational processes that predict positive student outcomes in order to support them. Thus, the main purpose was to determine a predictive model of disciplined behaviors and academic performance in Physical Education students. The Achievement Goal Theory and Self-Determination Theory acted as the theoretical framework. A total of 919 Spanish secondary school students participated in the study. The studied variables were: task-oriented motivational climate, basic psychological needs, autonomous motivation, disciplined behavior and academic performance. Data collection included Spanish validated questionnaires. The Mplus statistical program was used to perform a structural equations model of prediction. It included antecedents (task-oriented climate), motivational processes (basic psychological needs and autonomous motivation) and consequences (disciplined behavior, Physical education and overall students’ performance). The results revealed that positive results (discipline and academic performance in Physical Education) were positively predicted by autonomous motivation; autonomous motivation was positively predicted by basic psychological needs and these, in addition, by the task-oriented climate. The results highlighted the importance of the task-oriented motivational climate and the mediating role of the basic psychological needs and autonomous motivation in order to generate these positive student outcomes in Physical Education. This study could be a useful resource for teachers, since it offers the motivational variables that lead students to achieve disciplined behaviors and academic performance in Physical Education. Intervention programs based on the results of the present study could be applied in Physical Education classes in order to obtain better behavioral but also cognitive positive student outcomes.